2013
DOI: 10.1007/s00264-013-2174-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and clinical results after surgically treated tibial plateau fractures at three and twenty two years postsurgery

Abstract: Purpose We examined the development of osteoarthritis (OA) and post-traumatic bone loss after surgery for tibial plateau fractures (TPF). Methods Patients who had participated in previous follow-up (FU) examinations after TPF and primary reduction and internal fixation were re-evaluated. At the first FU, a median of three years after the accident (short-term FU), the patients underwent functional assessments and standardised X-rays to grade radiological OA and post-traumatic bone loss. At the second FU, a medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
2
16
0
1
Order By: Relevance
“…In our series, the observed rates were comparable. Clinical results seen in the literature are comparable to ours, emphasizing the severity of these lesions and the absolute necessity of a quality reduction [31,32]. Mobility and functional scores that we reported were satisfying and identical irrespective of the type of plate.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our series, the observed rates were comparable. Clinical results seen in the literature are comparable to ours, emphasizing the severity of these lesions and the absolute necessity of a quality reduction [31,32]. Mobility and functional scores that we reported were satisfying and identical irrespective of the type of plate.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, the clinical tolerance of locking plates was rarely studied, even though this was discusses by Hasan et al [11]. The different studies showed at the most the number of material ablations, with different figures ranging from 5 to 11 % [14,17,[25][26][27][28][29][30][31][32][33][34][35][36]. Concerning clinical tolerance, our hypothesis was confirmed with a better clinical tolerance for 3.5-mm plates, which has never been discussed in the literature.…”
Section: Discussionsupporting
confidence: 84%
“…Osteoarthritis was present in 40.6% of all patients, even as high as 57.5% in bicondylar fractures, and in 7.3% total knee arthroplasty was eventually required. Comparable results of OA [7][8][9][10][11][12][13] and total knee arthroplasty [15,27,28] are found in the literature.…”
Section: Discussionmentioning
confidence: 70%
“…Incidences of OA after tibial plateau fractures vary in literature between 10% and 58% [7][8][9][10][11][12][13]. Patients often present with limbspecific and general health deficits at follow-up [5].…”
Section: Introductionmentioning
confidence: 99%
“…47 In this group, persistent pain is related to high-energy trauma injuries. Another study 48 comparing OA signs at 3 and at 22 years in a group of 31 patients with surgically treated TPF, showed that there is a deterioration of radiological OA signs between 3 and 22 years of follow-up and that there are differences in the evolution of the OA signs between the operated and the healthy knee in the same patient. TKA was required in 13% of patients in this study.…”
Section: What Outcomes Can Be Expected?mentioning
confidence: 99%